The relationship between Body Mass Index and Body Fat percentage, estimated by bioelectrical impedance in a group of Romanian female students - Vrabie Diana; Iacob George-Sebastian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Bioelectrical impedance analysis (BIA) also called bioelectrical impedance (BEI) is a non-invasive method based on the electric conductibility properties of tissues and is a commonly used technique for estimating body composition.Percentage of body fat is strongly associated with the risk of several chronic diseases but its accurate measurement is difficult. Body Mass Index is a useful population-level measure of overweight and obesity. It is used for all categories of people, male or female.The main objective of this study was to determine if there is a relationship between BMI and body fat percentage (BF%) in a group of Romanian female students. This relationship has been studiedin various ethnic groups before. To conduct the study, we examined 29 young females (aged 20-36 years old) estimating BF% from bioelectrical impedance analysis using Tanita Body Fat Monitor Scale UM-076.In this research group, the BMI and BodyFat dependent variables have a moderate to strong correlation (r = .839; 0.75 < r < 1), the favorable score for the first measurement being a statistically relevant benchmark for the second (sig < 0.05).